General ontology for internet of things (goiot) to achieve semantic interoperability using sensor, observation, sample and actuator (sosa) approach - Fahad, Qaswar (2023)
Internet of Things (IoT) devices are increasing day by day, thus a common vocabulary is required to make sure these devices from a different manufacturer can communicate with each other by themselves known as semantic interoperability. Ontology is required to solve the semantic interoperability problem of the IoT. Ontology provides a base to represent objects in a specific domain. Classes, Instances, and Relationships are the components required to built ontology. Problems with existing IoT ontologies are as follows: (i) Incomplete IoT Concepts; (ii) Most of the Existing IoT ontologies did not includes all critical elements of IoT; (iii) The existing ontologies are not built on the latest ontology language standard recommended by W3C which is Web Ontology Language (OWL); (iv) The IoT ontologies in literature did not follow any Evaluation Measurement such as Reasoner. The objective of this research is to study the existing literature about IoT and Ontology and their relationship. Then to develop and evaluate GoIoT by using Protégé and pallet reasoner respectively. The methodology is divided into three portions which are Analysis, Development and Implementation, and Evaluation and Measurements. In the analysis part, basic concepts of IoT and Ontology are discussed. In Development and Implementation, SOSA is adopted to create a new ontology, namely GoIoT. It talks about the existing reused IoT concept and how new IoT concepts are further integrated. Further, it discusses which language and tools are used to build this ontology. The newly constructed GoIoT is evaluated via semantic reasoner and experts. The reasoner results showed zero error in GoIoT ontology which simply means that no issue is found among ontology components. Five (5) experts have also evaluated ontology in terms of nine (9) evaluation criteria. The mean value of five (5) expert combine is 83.059 % and this value shows that the Ontology developed can be accepted as Ontology that represent General Ontology for IOT.